Models and Hardware Implementation of Methods of Pre-processing Images Based on the Cellular Automata - Bilan, Stepan (European Journal of Applied Sciences, 2014)
The paper deals with the organization and construction of cellular automata for the implementation of the basic operations of the pre-processing images. The methods of edge detection, zoom, filling inside area of images and also selection of objects are considered. The analysis of the impact of different forms of the neighboring cells for the effective execution of operations is carried. Programs that simulate the operation of CA are developed. Computer models of the main elements in CAD Active-HDL have been obtained by modeling the structure of the CA. The obtained models have passed the test and their analysis showed high reliability of operation. This allows us to implement them in modern CPLD and FPGA hardware. This hardware is easily reprogrammed under the given structure of CA. Implementing FPGAs allows us to use one chip for realization of the basic functions of the CA. The experimental results showed that the used methods and CA are highly effective. The use of CA allows to describe of the image with high speed highly effective.